Analyzing Of Under Five Children Aspect To Acute Respiratory Infection Disease (ARI) In Indonesia: Meta-Analysis 2015-2020 - Hasanah, Swara Mega (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2022)
Acute Respiratory Infection (ARI) is one of the health problems that exist in developing and developed countries. The proportional mortality rate (PMR) due to ARI in children under five in the world is 16%, two-thirds of deaths are infant deaths. The mortality rate is very high in infants, children and the elderly, especially in developing countries. The purpose of this study was to analyze the intrinsic risk factors for the characteristics of children under five in Indonesia. The method in this study uses meta-analysis, which is a statistical method that combines several (two or more) research results quantitatively by looking for effect size values or summaries using JASP software version 0.9.2. Sources of data in this study came from Google Scholar, Science Direct, and Pubmed then sorted according to inclusion and exclusion criteria and obtained 37 research articles. The result of the meta-analysis that has the highest risk factor for the variable characteristics of children under five is the nutritional status variable with a pooled PR value of e0.30 = 1.350 (95% CI 0.03 – 0.58), then the variable age under five with a pooled PR value of e0.16 = 1.174 (95% CI -0.40 – 0.72) and the lowest variable for the characteristics of children under five was found in the sex of children under five with a pooled PR value of e0.08 = 1.083 (95% CI -0.04 – 0.19). The conclusion from the results of the meta-analysis that has the highest level of risk is the nutritional status of children under five, age of toddlers, and gender. It is hoped that the puskesmas can make efforts to control the risk of ARI occurrence in toddlers by conducting periodic counseling.